Healthcare Professionals' Perspective on Palliative Care in Intensive Care Settings: An Interpretive Descriptive Study - Hanan Hamdan Alshehri; Axel Wolf; Joakim Öhlén; Sepideh Olausson (SAGE Publishing, 2022)
There is a growing need to integrate palliative care into intensive care units and to develop appropriate knowledge translation strategies. However, multiple challenges persist in attempts to achieve this objective. In this study, we aimed to explore intensive care professionals' perspectives on providing palliative and end-of-life care within an intensive care context. We used an interpretive description approach and interviewed 36 intensive care professionals at four hospitals in Saudi Arabia. Our findings reflect a discourse about end-of-life care driven by a do-not-resuscitate classification and challenges associated with family involvement in care goals. We provide key insights of importance for the development of strategies for the integration and knowledge translation of palliative care into intensive care contexts.